Genome wide association study to identify the genetic base of smallholder farmer preferences of Durum wheat traits - Kidane, Yosef Gebrehawaryat; Mancini, C.; Mengistu, D.K.; Frascaroli, E.; Fadda, Carlo; Pe, M.E.; Dell'Acqua, M. (Frontiers Media, 2017)
Smallholder agriculture involves millions of farmers worldwide. A methodical utilization of their traditional knowledge in modern breeding efforts may help the production of locally adapted varieties better addressing their needs.